Research-oriented model of cognitive learning in the subject of Technique (R&E-SOURCE, 2025)
This article focuses on the research-oriented model of student education in the subject of Technique in lower secondary education in the Slovak Republic. The proposed model reflects the long-term educational needs in the subject of Technique, which, despite updates to the curriculum in the Educational Standard of the subject, have yet to be fully addressed. The learning model includes worksheets for students that feature experiments, along with a methodology for carrying out each experiment. Students discover new knowledge through research activities during the experiment, which they then evaluate at the end of the worksheet. The worksheet also includes a self-assessment sheet, where students record their responses to the experiment, reflect on their understanding of the content, and assess their satisfaction with their performance.The article also presents the results of empirical research aimed at verifying the proposed research-oriented model. This research is part of the KEGA project No. 006UMB-4/2022, conducted in 2022.